(untitled) (Third Sector Social Economic Review, 2024)
In this study, it is aimed to measure the value of the brand concept, which is not only a symbol on the product packaging, but also of vital importance for companies. The concept of brand and the measurement of its value, which can be effective in the processes of appealing to the sense of trust and perception of customers, gaining their loyalty and creating awareness in the sector, which are among the most important objectives of businesses, are in the scope of investigation of finance science as well as in the research field of marketing science. In today’s increasingly competitive environment, the brand, which can directly shape consumer behavior and be decisive in creating loyal customers, is an important concept that can affect the cash flow and survival of businesses. Within the scope of the study, the Hirose Model was used to measure the brand value of the chain supermarket companies listed on the BIST, which constitute the sample of the study, and the results were compared with Brand Finance report data. As a result of the calculations made with the Hirose Model, Bim is the chain supermarket company with the highest financial brand value in the 5-year period between 2018 and 2022, while Carrefour is the company with the lowest brand value. When the calculation results and Brand Finance reports are considered together, it is seen that there is no difference in terms of ranking according to the Hirose Model, but there is a difference in terms of amounts. It can be said that the reason for this is that the Hirose Model is based only on finance-oriented financial data, while Brand Finance reports are based on consumer behavior as well as finance-oriented data.